(untitled) (Plant Tissue Culture and Biotechnology, 2019)
In genetic improvement of mungbean much success has not been achieved due to its recalcitrant nature towards in vitro regeneration. An attempt was made to develop an Agrobacterium-mediated in planta genetic transformation protocol for a locally grown mungbean variety BARI Mung-3 using a screenable marker gene. Two minutes of vacuum infiltration followed by 60 minutes of incubation period in Agrobacterium suspension of Winans’ AB medium containing wounded tobacco leaf extract was found most suitable towards genetic transformation in pricked de-coated half seed explants. An optical density (OD600) of 0.7 was found most effective for transient gus gene expression. Chimeric GUS expression was observed in the root and leaf tissues from the successfully transformed plantlets obtained through in planta transformation. This methodology of genetic transformation was found more suitable, easier and less time consuming than tissue culture based genetic transformation, which may be used for the genetic improvement of mungbean.